2014
DOI: 10.1039/c4tx00007b
|View full text |Cite
|
Sign up to set email alerts
|

The mutagenic effects of 2-amino-1-methyl-6-phenylimidazo[4,5-b] pyridine in Muta™Mouse colon is attenuated by resveratrol

Abstract: Epidemiology studies show that consumption of certain naturally occurring chemicals (generally plant-derived) can protect against the development of cancer (chemoprevention).Resveratrol, a phytoalexin found in foods such as grapes and wine as a glucoside , is one such chemical. Our group has previously shown that treating mammalian cells with resveratrol aglycone can reduce the mutagenicity of the cooked meat-derived carcinogens 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) and 2-amino-1-methyl-6-pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The DNA adducts can eventually lead to mutations. Indeed, in a variety of bacterial and mammalian systems PhIP was demonstrated to be a DNA damaging and mutagenic agent (Felton and Knize, 1991) YadollahiFarsani et al, 1996), (Boyce et al, 2004;Boyce, 2014). The DNA-damaging and mutagenic properties of PhIP are therefore one mechanism by which the chemical can cause cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA adducts can eventually lead to mutations. Indeed, in a variety of bacterial and mammalian systems PhIP was demonstrated to be a DNA damaging and mutagenic agent (Felton and Knize, 1991) YadollahiFarsani et al, 1996), (Boyce et al, 2004;Boyce, 2014). The DNA-damaging and mutagenic properties of PhIP are therefore one mechanism by which the chemical can cause cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The genotoxicity of PhIP is well established (Boyce et al 2014 ; Brooks et al 1994 ; Lynch et al 1998 ; Yadollahi-Farsani et al 1996 ). In the present study, we have assessed genotoxicity using an adapted micronucleus assay and show that PhIP is a potent inducer of micronuclei in ER receptor-positive MCF-7 cells but not MDA-MB-231 cells (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In an in vivo study, PhIP produced mutation in the colon of male rats more obvious than females. It was also shown that the antimutagenic effects of RSV might be associated with metabolic activation of PhIP, because RSV strongly suppressed ethoxyresorufin‐O‐deethylase activity in vivo (Boyce, David, & Gooderham, ).…”
Section: Chemical‐induced Toxicitymentioning
confidence: 99%